Experimental Medications Made with Сetraria islandica Showing Antiviral Activity against Influenza A Virus - E. V. Makarevich; M. A. Protsenko; O. Yu. Mazurkov; E. I. Filippova; N. A. Mazurkova (Антибиотики и Химиотерапия, 2024)
Background. To date, virologists have identified more than 25,000 influenza virus А serotypes, and their number will increase in the future. Therefore, the development of new antiviral drugs will always be relevant.The aim of the study is to obtain and test the chemical composition and antiviral activity of the lichen Cetraria islandica extracts against the influenza A virus.Material and methods. Samples of lichen Cetraria islandica (aqueous and ethanol extracts) were tested for toxic properties and antiviral activity against influenza A virus in MDCK cell culture.Results. Samples of aqueous and ethanol extracts of Cetraria islandica were obtained; their chemical composition was described. In MDCK cell culture, the extracts exhibited antiviral activity against human influenza virus А/H3N2 and avian influenza virus А/H5N1. When studying the mechanism of action of Cetraria islandica extracts, it was noted that Cetraria islandica samples possess pronounced antiviral properties against avian influenza A/chicken/Kurgan/05/2005 (H5N1) and human influenza A/Aichi/2/68 (H3N2) at the stage of their adsorption and reproduction.Conclusions. Samples of Cetraria islandica have antiviral activity at the stage of adsorption and reproduction of influenza A virus in MDCK cell culture. The ethanol extract shows a higher antiviral efficacy compared to the aqueous extract.